The daily discoveries of a Bible scholar and manuscript hunter a biography of James Rendel Harris (1852-1941) - Falcetta, Alessandro 1971- (London Bloomsbury Publishing PLC, 2018)
Intro -- Title page -- Copyright Page -- Dedication Page -- Contents -- List of Maps -- List of Illustrations -- Preface -- Acknowledgements -- Abbreviations -- Author's Note -- Maps -- Prologue -- Chapter 1: Between Two Rivers -- Plymouth -- Harris and Budd -- Nonconformity -- Growing up in Plymouth -- Education -- Chapter 2: From Math to Hort -- Mathematics -- Clare College -- The Triumvirate -- The Greek New Testament of Hort and Westcott -- Conversion to Textual Criticism -- Controversies -- Darwin -- Chapter 3: Conversion -- Evangelical Revival -- David B. Updegraff's Religious Experiences -- Forgiveness -- Sanctification -- The Nonconformist Vanguard -- Emmanuel Congregational Church -- Memoranda Sacra -- Chapter 4: Helen -- Quakerism -- Marriage -- Balkwill -- Helen before Rendel -- Chapter 5: A Promising Scholar -- Itinerant Preachers -- The Johns Hopkins University -- New Testament Autographs and Other Essays -- A Tour of European Libraries -- Social and Religious Engagements -- The Vivisection Controversy -- Chapter 6: A Popular Professor -- Waiting in Cambridge -- Membership in the Society of Friends -- Back to the States -- Work at Haverford -- Lack of Scholarly Facilities -- Chapter 7: The Dark Closet -- The Manuscript Hunter -- Tischendorf and Codex Sinaitcus -- Hatching Plans -- Eastbound -- Cairo -- Brummana -- Manuscripts on the Mountains -- Jerusalem -- The Monastery of St Catherine -- A Tour of Palestine -- Chapter 8: The Call of the Cam -- The Haverford Manuscript Collection -- Edition of Texts -- The Publication of the Acts of Perpetua and Felicitas -- The Publication of the Apology of Aristides -- Work on Codex Bezae -- Back to Cambridge -- Lectureship in Palaeography -- Chapter 9: The Septuagint Mission -- The Septuagint -- Palestine -- Asia Minor -- Greece -- Chapter 10: With the Sisters of Sinai -- Lewis and Gibson
An Old Syriac Version of the Gospels -- The Journey to St Catherine's -- Frictions -- The Transcription of the Palimpsest -- Work on Other Manuscripts -- Departure -- News of the Discovery -- The First Edition of the Palimpsest -- Lewis's Own Edition of the Palimpsest -- Chapter 11: The Breeze of Cambridge -- Palaeography Class -- Outspoken Nonconformist -- Magdalena and Editha Blass -- Lecturing Tours -- Retirement Plans -- Chapter 12: The Origins of the Text of the New Testament -- The Ferrar Group -- Codex Bezae -- The Diatessaron of Tatian -- Hermas in Arcadia -- The Story of Aḥiḳar -- Hastings's Dictionary of the Bible -- Chapter 13: The Sword of the Sultan -- The Abdul Hamit Massacres -- The Launch of the Expedition -- Constantinople -- Ayntab -- Urfa -- Siverek -- Mardin -- Diyarbekir -- Harput -- Malatya -- Rendel's Homebound Journey -- Harput and Arapkir -- Egin -- Chapter 14: Back to the Ourfans -- A Conference on Missionary Work -- Helen's Journey to Berlin and St. Petersburg -- Supervision of the Orphanages -- A New Journey to Armenia -- The Way to the Interior -- Van -- Bitlis -- Harput -- Egin -- Malatya -- Urfa -- Back to Constantinople -- Chapter 15: Leyden's Dis-appointment -- The Boer War -- Helen's Journey to the Concentration Camps -- Helen's Opinion on the Camps -- The Leyden Appointment to a Professorship -- Leyden's Disappointment -- The Reason for the Refusal -- Chapter 16: The Quaker Renaissance -- The Theological Debate -- The Manchester Conference -- The Scarborough Summer School -- Mürren -- Chapter 17: The Foundation of Woodbrooke -- George Cadbury -- The Woodbrooke Scheme -- The Appointment of Rendel -- Leyden in the Way -- The Freedom of Woodbrooke -- Chapter 18: The Doctor in Wonderland -- The First Term -- The Dictator of Studies -- Mary Snowden Braithwaite -- Lectures and Lecturers -- The Selly Oak Colleges
The Woodbrooke Spirit -- The Netherlands -- Norway -- Chapter 19: Inner Light -- The Scholar -- The Teacher -- The Spiritual Man -- The Woodbrooke Liturgies -- The Inward Light -- The Guiding Hand of God -- The Continuity of Inspiration -- Quaker and Evangelical -- Chapter 20: President of the Free Churches -- Domesticities -- The Letter Writer -- The 1910 American Lecturing Tour -- Honorary Degrees -- Work for the Free Churches -- The 1903 Education Act -- President of the NCEFC -- Aaron's Breastplate -- Chapter 21: The Crumbling Empire -- The First Balkan War -- Armenian Relief -- After the Genocide -- Lootfy Levonian -- Araxia Jebejian -- Chapter 22: The End of a World -- The International Outlook -- Delegation to Germany -- Responding to Conflict -- Conscientious Objectors -- Woodbrooke during the War -- Helen's Departure -- Time to Leave -- Farewell to Woodbrooke -- The Suffering and the Glory -- Chapter 23: Ulysses -- Moulton's Invitation to India -- The City of Birmingham -- Tourist in Egypt -- Papyri Hunt in Cairo -- The Fayyum and Oxyrhynchus Papyri -- Last Excursions -- The City of Paris -- Corsica -- Home -- Chapter 24: Manuscripts -- The Rylands Greek Papyri -- The Harvard Syriac Manuscripts -- Sources of Manuscripts -- Alpheus N. Andrus -- The Diatessaron Quest -- Alphonse Mingana -- Chapter 25: The Odes of Solomon -- The Discovery of the Odes of Solomon -- The Significance of the Odes of Solomon -- Chapter 26: The Origins of Christianity -- Away from Textual Criticism -- Early Christianity -- Studies in Testimonies -- Jesus the Wisdom of God -- Origins of the Eucharist -- The Antitheses of Marcion -- On the Quest for Quadratus -- The Art of Conjectural Emendation -- Chapter 27: The Origins of Religion -- The Heavenly Twins -- Boanerges -- Reception of the Twin Studies -- James G. Frazer -- Twins among the Twelve
The Cult of the Greek Gods -- A Mercurial Scholar -- Chapter 28: The Curator -- Manuscripts to Manchester -- Curator at the Rylands Library -- At Home -- Adolf Harnack -- Adolf Deissmann -- The Tercentenary of the Mayflower -- The Mayflower University -- The History of the Pilgrim Fathers -- As Pants the Hart -- Chapter 29: The Quest for the Harmony -- The Last Expedition to Sinai -- Constantinople -- Lebanon -- Jerusalem -- Cairo -- Sinai -- Work at the Monastery -- Wadi Natrun -- Chapter 30: The Rendel Harris Library -- A New Family -- Holidays -- A New House -- The Rendel Harris Library -- The Woodbrooke Museum -- The Holy Grail -- Chapter 31: The Mingana Collection -- Mingana's First Journey -- Mingana's Second and Third Journey -- The Mingana Collection -- The Arrangement of the Collection -- Mingana the Scholar -- Mingana and Rendel -- Chapter 32: The Blind Master -- Travels -- Recognitions -- Failing Health -- Family and Friends -- Sherlock's Assistance -- The Bezan Club -- Colleagues -- J. Enoch Powell -- Chapter 33: The Origins of Civilization -- Collections of Essays -- Sundry Studies -- The Hunt for Place-Names -- The Arabians, the Celts and the Hittites -- The Diffusion of Egyptian Civilization -- Egyptian Colonies -- The Influence of Egyptian Myths -- The Routes of Colonization -- The Basques -- Moses -- 'A Perilous Thinker' -- Chapter 34: The Last Discovery -- The Outbreak of the Second World War -- Clydesdale Hotel -- The Last Days -- Memorial Speeches -- Epilogue -- Notes -- Prologue -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Chapter 12 -- Chapter 13 -- Chapter 14 -- Chapter 15 -- Chapter 16 -- Chapter 17 -- Chapter 18 -- Chapter 19 -- Chapter 20 -- Chapter 21 -- Chapter 22 -- Chapter 23 -- Chapter 24 -- Chapter 25 -- Chapter 26
Chapter 27 -- Chapter 28 -- Chapter 29 -- Chapter 30 -- Chapter 31 -- Chapter 32 -- Chapter 33 -- Chapter 34 -- Epilogue -- Bibliography -- Works of James Rendel Harris -- Works of Helen Balkwill Harris -- Other Works -- Index
Keywords: Biografie